Poly(butylene succinate-ran-ε-caprolactone) copolyesters: Enzymatic synthesis and crystalline isodimorphic character. (October 2017) - Ciulik, Claudio; Safari, Maryam; Martínez de Ilarduya, Antxon; Morales-Huerta, Juan Carlos; Iturrospe, Amaia; Arbe, Arantxa; Müller, Alejandro J.; Muñoz-Guerra, Sebastián
Graphical abstract: Highlights: Poly(butylene succinate- ran -ε-caprolactone) copolyesters were obtained by enzymatic ROP. Cyclic butylene succinate oligomers and ε-caprolactone were used as feed monomers. These random copolymers are semi-crystalline over the entire range of compositions. Crystallization studies by DSC, PLOM and WAXS showed that these copolymers are isodimorphic. They display a pseudo-eutectic region with double crystalline phases. Abstract: In this paper, the preparation of PBS- ran -PCL copolyesters by enzymatic ring opening polymerization is presented for the first time. The copolyesters were produced in a wide composition range and free of metallic contaminants, so they may be regarded as potential biomaterials. The copolymers have been characterized by proton and carbon nuclear magnetic resonance ( 1 H and 13 C NMR), gel permeation chromatography (GPC), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC), polarized light optical microscopy (PLOM) and wide angle X-ray scattering (WAXS). The PBS- ran -PCL copolyesters were able to crystallize in the entire composition range and displayed a pseudo-eutectic region. Most copolymers away from the pseudo-eutectic region exhibited a single crystalline phase (PBS-rich or PCL-rich crystalline phase), while within the pseudo-eutectic region the copolymers were double crystalline. Observations by PLOM, during isothermal crystallization showed that both nucleation density and spherulitic growth rate of the copolyesters are determined by the component that constitutes the majority phase. WAXS studies revealed that d spacings of selected crystallographic planes depend on composition. Therefore, both DSC and WAXS results suggest that the copolymers are probably isodimorphic, as the PBS-rich crystalline phase may contain small inclusions of PCL co -units, while the PCL-rich crystalline domains may also contain a minor quantity of PBS co -units inside.